Effect of Enteral Immunonutrition in Patients Undergoing Surgery for Gastrointestinal Cancer: An Updated Systematic Review and Meta-Analysis - Shen, Jingyi; Dai, Senjie; Li, Zongze; Dai, Wei; Hong, Jiaze; Huang, Jin; Chen, Jingjie (Frontiers in Nutrition, 2022)
Background: The efficacy of enteral immunonutrition (EIN) in patients undergoing gastrointestinal cancer surgery remains debatable. This meta-analysis aimed to investigate the effectiveness of EIN administration in patients undergoing surgery for gastrointestinal cancer. Methods: From January 2000 to January 2022, PubMed, EMBASE, Cochrane Library, and Web of Science were thoroughly searched for randomized controlled trials (RCTs) with EIN versus standard diet or no supplement in patients undergoing surgery for gastrointestinal cancer. Overall complications and infectious complications were the primary outcomes. The secondary results were non-infectious complications, mortality, length of hospital stay, and enteral nutrition-related complications. Results: Thirty-five studies reporting 3692 patients undergoing surgery for gastrointestinal cancer (including gastric cancer, colorectal cancer, oesophageal cancer, periampullary cancer, or pancreatic cancer) were included. Compared with the control group, EIN group had a significantly decreased incidence of overall complications (RR=0.79, p<0.001). Infectious complications in patients who received EIN were considerably lower than in the control group (RR=0.66, p<0.001). Compared to the control group, the incidence of surgical site infection, abdominal abscess, anastomotic leakage, bacteremia, duration of systemic inflammatory response syndrome (SIRS), and duration of antibiotic therapy was significantly lower in the specific infectious complications treated with EIN. Still, there was no significant difference between the two groups with other infectious complications. Moreover, a substantial shortening in the length of hospital stay was shown in EIN group compared with the control group. Still, no significant effect of EIN was demonstrated in non-infectious complications and mortality. The enteral nutrition-related complications had no significant difference between the two groups. Conclusions: EIN is safe and effective in reducing overall complications, infectious complications, and hospital stay in patients undergoing gastrointestinal cancer surgery (including gastric cancer, colorectal cancer, oesophageal cancer, periampullary cancer, or pancreatic cancer).